Pengaruh Current Ratio, Debt to Equity Ratio dan Total Asset Turnover terhadap Return on Asset Perusahaan Perbankan - Amalia, St. Reski; Arifin, Muhammad Riski; Hariati; Asnandar, Hairul; Syahriadin B, Muh.; Rahmat, Wahidin; Muchran, Muchriana (SINOMIKA JOURNAL: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2026)
This study aims to examine the effects of the Current Ratio (CR), Debt-to-Equity Ratio (DER), and Total Asset Turnover (TATO) on Return on Assets (ROA) among banking companies listed on the Indonesia Stock Exchange during the 2020–2025 period. The population consisted of 16 banking companies observed over six years, resulting in 96 firm-year observations. The study employed a quantitative approach using secondary data obtained from the companies’ annual financial reports. Multiple linear regression analysis was applied to evaluate the relationship between the independent variables and Return on Assets. The results indicate that the Current Ratio has no significant effect on Return on Assets, suggesting that the level of short-term liquidity does not directly determine the profitability of banking companies. In contrast, the Debt-to-Equity Ratio has a significant effect on Return on Assets, indicating that the companies’ financing structure influences their ability to generate profits from their assets. Total Asset Turnover also has a significant effect on Return on Assets, demonstrating that the efficiency of asset utilization plays an important role in improving financial performance. These findings highlight the importance of effective capital structure and asset management in enhancing the profitability of banking companies.